Sociodemographic determinants of medical termination of pregnancy along with contraceptive practices - Karale, Anand; Shinde, Kunaal K.; Risbud, Neelesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Though the most common reasons for medical termination of pregnancy (MTP) is unwanted pregnancy due to nonuse of contraceptives by the women of reproductive age group and other are pregnancy before marriage or due to rape. Several studies indicate that most abortions are sought to limit family size or space the next pregnancy. There is need to study relation of MTP with contraceptive practices. Methods: The present cross-sectional study was conducted at Smt. Kashibai Navale Medical College and General Hospital, Narhe, Pune, to study socio-demographic factors associated with medical termination of pregnancy and its relation with contraceptive practices. Total 1840 women seeking care for medical termination of pregnancy were interviewed after their informed consent during period of January 2015 to December 2017. A detailed history regarding age, religion, income, marital status, parity, history of previous MTP, indications for MTP, use of contraception, gestational age was taken. Results: Statistical analysis-chi square test of significance for qualitative data using SPSS software version 24.0. The proportion of women coming for MTP due to nonuse of contraceptives was 86% the other indications for MTP were medical condition (9%) and contraceptive failure (5%). The factors like age, religion, education and socioeconomic status were significantly associated with MTP. Conclusions: There is need to counsel women of reproductive age group that MTP is not a way to control unwanted birth.